Neonatal morbidities and postnatal growth failure in very low birth weight, very preterm infants. (8th May 2022) - Ofek Shlomai, Noa; Reichman, Brian; Zaslavsky‐Paltiel, Inna; Lerner‐Geva, Liat; Eventov‐Friedman, Smadar; ,
Abstract: Aim: To assess postnatal growth in infants with and without major neonatal morbidities. Methods: This study is based on analysis of data collected by the Israel Neonatal Network on VLBW infants (≤1500 g) born in Israel from 2009 to 2018. Postnatal growth was assessed in two 5 years epochs: 2009–2013 ( n  = 4583) and 2014–2018 ( n  = 4558). Outcome was considered as severe, mild and no postnatal growth failure (PNGF). Morbidities included respiratory distress syndrome, bronchopulmonary dysplasia, necrotising enterocolitis, patent ductus arteriosus and grades 3–4 intraventricular haemorrhage. Multinomial logistic regression analyses with the generalised estimating equation approach were applied. Results: The study population composed 9141 infants. Of them, 2089 had at least one major morbidity and 7052 infants had none. In infants with no morbidities, 2.1% had severe PNGF, 23.7% mild PNGF and 74.2% had no PNGF, as compared to 13.6%, 43.9% and 42.5%, respectively, in infants with any major neonatal morbidity ( p  < 0.0001). Conclusion: Despite enormous advances in neonatal care, postnatal growth remains a challenge in VLBW infants, particularly in infants with major neonatal morbidities. Along with efforts to decrease morbidity, a more personalised plan and follow‐up may be required in infants with major morbidities, given their high risk for diminished growth and potentially, adverse neurodevelopmental outcomes.